Copper-based / solid solution catalyst for hydrogen production by methanol reforming and preparation method and application of copper-based / solid solution catalyst
By using co-precipitation method and impregnation method in the methanol water vapor reforming hydrogen production catalyst, and loading 7% CuO, the problem of increased CO selectivity of the catalyst under high temperature conditions is solved, and a catalyst with low CO selectivity and high reactivity is achieved, which is suitable for proton exchange membrane fuel cells.
Patent Information
- Application Number
- CN202411759154.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-25
AI Technical Summary
The existing methanol water vapor reforming hydrogen production catalyst has a rapid increase in CO selectivity under high temperature conditions, resulting in a toxic effect on proton exchange membrane fuel cells and failing to effectively regulate the solubility and number of active sites of Zn2+ in the ZrO2 lattice.
The solid solution support ZnxZr1-xOy was prepared by co-precipitation method and impregnation method, and 7% CuO was loaded by XRD and XPS extrapolation methods to form a Cu-based catalyst, and the Zn/Zr molar ratio was regulated to optimize the catalytic performance of the catalyst.
The catalyst used in proton exchange membrane fuel cells has low CO selectivity, high methanol conversion, and good thermal stability and reactivity.
Smart Images

Figure CN119680556A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy catalysis and relates to a method for preparing a Cu-based catalyst using a solid solution as a carrier for use in a methanol reforming hydrogen production energy cell and an XRD extrapolation method for exploring the influence of ZnO lattice capacity on reaction performance. Background Art
[0002] Hydrogen is considered to be an efficient and clean energy source with great application prospects. In particular, the application of proton exchange membrane fuel cells (PEMFC) fueled by hydrogen in mobile systems has attracted widespread attention. However, due to the limitations of hydrogen in the transportation process, hydrogen is generally produced in situ by reforming alcohols and hydrocarbons. Compared with other hydrogen storage carriers, methanol is one of the best raw materials for hydrogen production because of its low cost, easy conversion, and sulfur-free. On the other hand, since CO is toxic to fuel cells, the product CO content in hydrogen production by methanol steam reforming is low, which is a significant advantage for the application of PEMFC.
[0003] Existing studies have shown that due to differences in ionic radius, electronegativity and valence state of two metal oxides, solute ions often have a certain solubility in the solvent oxide, thus forming a solid solution structure. Solid solution catalysts are widely used in catalytic methanol steam reforming to produce hydrogen, and have better catalytic performance than single-component metal oxides.
[0004] In the field of methanol steam reforming hydrogen production solid solution catalyst, Chen et al. (Methanol Steam Reforming over ZnO / ZnZrOx: Performance Enhanced with a Cooperative Effect[J]. Chemcatchem, 2022, 14(1): 1867-3880.) found that ZnZrO x Solid solution as a support is better than single metal oxide ZrO 2 As a carrier, it can more effectively inhibit the formation of CO. At the same time, ZnO and ZnZrO x The synergistic effect of the solid solution improves the performance of the catalyst. There is a volcano-like trend between the methanol conversion and CO selectivity and the Zn / Zr ratio, but no quantitative analysis of the Zn / Zr ratio is available. 2+ In ZrO 2 The solubility in the lattice of Zn / Zr was not studied, and the relationship between the number of active sites and the Zn / Zr ratio was not considered. In addition, in the solid solution catalyst, Das Dipak et al. (Methanol steam reforming behavior of copper impregnated over CeO 2 -ZrO 2derived from a surfactant assisted coprecipitation route [J], International Journal of Hydrogen Energy, 2015, 40(33):10463-10479.) found that the copper particles covered by coke were the cause of the catalyst performance degradation when they decomposed into the oxidized state (Cu 2+ ) and reduced state (Cu 0 and Cu + ), the catalyst performance is improved. This indicates that Cu + / Cu 0 The ratio and the change of copper crystal phase are the main factors affecting the reaction performance. However, after the reaction temperature reaches 275℃, the CO selectivity of the catalyst increases rapidly, and its concentration far exceeds 10ppm, which will have a serious toxic effect on the proton exchange membrane fuel cell. Summary of the invention
[0005] The purpose of the present invention is to provide a copper-based / solid solution catalyst for hydrogen production from methanol reforming, a preparation method and an application thereof. The active component copper is loaded on a solid solution carrier near the lattice capacity threshold, and the catalyst has the best catalytic performance, the strongest interaction between the metal and the carrier, and can be used in proton exchange membrane fuel cells.
[0006] The copper-based / solid solution catalyst for methanol reforming to produce hydrogen according to the present invention is a solid solution Zn x Zr 1-x O y The Cu-based catalyst as a carrier has a molecular formula of 7%CuO / Zn x Zr 1-x O y , wherein x=0.1~0.7, preferably x=0.4.
[0007] The copper-based / solid solution catalyst for methanol reforming to produce hydrogen according to the present invention, when Zn x Zr 1-x O y Each gram of ZrO in the solid solution carrier 2 When the content of ZnO in the carrier is less than 0.457 g, the carrier appears as a tetragonal zirconium oxide crystal phase. When the solubility exceeds this value, the excess ZnO 2+ ZnO crystallites will be formed.
[0008] The method for preparing a copper-based / solid solution catalyst for hydrogen production from methanol reforming of the present invention first adopts a coprecipitation method to prepare Zn x Zr 1-x O yThe solid solution was used as the carrier, and then 7% CuO was loaded by impregnation method to obtain the final catalyst 7% CuO / Zn x Zr 1- x O y .
[0009] Specifically, the method for preparing a copper-based / solid solution catalyst for hydrogen production by methanol reforming described in the present invention is characterized by comprising the following steps.
[0010] (1) According to the Zn / Zr molar ratio, weigh Zn(NO 3 ) 2 ∙6H 2 O and Zr(NO 3 ) 4 ∙5H 2 O was placed in a beaker, and an appropriate amount of deionized water was added. The mixture was heated and stirred in a 90°C water bath to dissolve into a clear solution.
[0011] (2) The solution obtained in step (1) was added dropwise with 25-28 wt.% ammonia water while stirring to adjust the pH value to 9. After the precipitate was formed, it was stirred for 2 h, allowed to stand for 2 h, and then filtered and washed with deionized water until the TDS of the filtrate was less than 20 ppm.
[0012] (3) The filter cake obtained in step (2) was dried in an oven at 110°C for 12 hours, taken out, and ground.
[0013] (4) The product obtained in step (3) was placed in a muffle furnace and heated at a rate of 2°C / min. It was calcined at 550°C in an air atmosphere for 4 h to obtain Zn x Zr 1-x O y Solid solution carrier.
[0014] (5) Weigh the solid solution support and Cu(NO 3 ) 2 ∙3H 2 O is added into the crucible, and an appropriate amount of deionized water is added, stirred for 2 h, heated and stirred in a 90 °C water bath to evaporate to dryness, placed in a 110 °C oven until completely dried, and then ground.
[0015] (6) The product obtained in step (5) was placed in a muffle furnace and heated at a rate of 2°C / min, and calcined at 450°C in an air atmosphere for 4 h to obtain a Zn x Zr 1-x O y Solid solution as a supported Cu-based catalyst.
[0016] (7) Quantification of Zn using XRD and XPS extrapolation x Zr1-x O y Solute Zn in solid solution 2+ Ions in ZrO 2 Solubility in the lattice to obtain the optimal ratio of Zn x Zr 1-x O y Solid solution as a supported Cu-based catalyst.
[0017] Preferably, the theoretical dense monolayer capacity of CuO on the carrier is 0.196 g / 100m 2 , Zn was tested by BET characterization x Zr 1-x O y The specific surface area of the solid solution carrier is 35-40m 2 / g, from which it can be inferred that CuO in Zn x Zr 1-x O y The theoretical dispersion threshold on the solid solution support is 7% CuO, which is selected in Zn x Zr 1-x O y The best solution is to load 7% CuO on the solid solution carrier.
[0018] The copper-based / solid solution catalyst for hydrogen production from methanol reforming described in the present invention is used in hydrogen production from methanol steam reforming. The method comprises the following steps: 100 mg of a 40-60 mesh catalyst was placed in the reactor, and 10 vol% H was introduced at a flow rate of 30 mL / min at 1 atm and 300 °C. 2 / Ar mixed gas reduction for 40 minutes, the reaction temperature is controlled at 200-360℃, and the temperature is controlled by a thermocouple. 3 OH / H 2 The H O molar ratio was 1 / 1.5 and the flow rate was 0.05 mL / min. 2 O and CH 3 The OH mixture was injected into the vaporization chamber by a micro pump and the temperature was controlled at 200°C to completely evaporate the liquid into gas. The corresponding reaction space velocity (WHSV) was 42000 mL / h˙g cat Then, Ar was introduced into the reactor at a flow rate of 30 mL / min for reaction.
[0019] According to the results of the catalyst performance test, the CO selectivity of the catalyst is low. 2 As the main product of the catalyst, this has significant advantages for the application of proton exchange membrane fuel cells. The catalyst activity shows a "volcanic" trend, at the threshold of 7% CuO / Zn 0。4 Zr 0.6 O yThe catalyst has the best catalytic performance and the strongest interaction between the metal and the carrier. It achieves a methanol conversion rate of 96% at 360°C and a CO selectivity of only 1%.
[0020] The present invention prepares a series of 7%CuO / Zn with different Zn / Zr molar ratios. x Zr 1-x O y The XRD and XPS extrapolation method was used to accurately quantify the solubility of the solute ions in the solid solution support. The diffraction peak intensity of the ZnO (101) crystal plane in each catalyst was measured and divided by the ZrO 2 The diffraction peak intensity of the (111) crystal plane is obtained. ZnO / I ZrO2 The ratio is plotted against the ZnO content and a related straight line is fitted.
[0021] In order to obtain efficient methanol steam reforming hydrogen production catalyst, the present invention designs a series of 7% CuO / Zn catalysts by adjusting the Zn / Zr molar ratio. x Zr 1-x O y Catalyst. According to the catalyst H 2 -TPR test results show that when the ZnO content is below the lattice capacity threshold, the H 2 The reduction temperature gradually increases, indicating that the interaction between the metal and the support is stronger; when the ZnO content exceeds the lattice capacity threshold, H 2 The reduction temperature begins to decrease, and the interaction between the metal and the support begins to weaken. At this time, the 7%CuO / Zn 0。4 Zr 0.6 O y The interaction between the metal and the carrier of the catalyst is the strongest, the catalyst performance is the best, and stability tests have been conducted on it, showing good thermal stability.
[0022] Compared with the prior art, the catalyst prepared by the present invention has the following advantages.
[0023] (1) The raw material cost for preparing the catalyst of the present invention is low, the preparation process is simple and easy, the equipment requirements are low, the solvent is non-toxic and harmless, and there is no secondary pollution to the environment.
[0024] (2) The coprecipitation method and impregnation method used in the present invention for preparing the catalyst have simple and easy preparation process and the reaction process is easy to control.
[0025] (3) The Cu-based catalyst prepared by the present invention with a solid solution as a carrier has a volcanic trend in the catalyst performance in the methanol steam reforming hydrogen production reaction, and the catalyst at the threshold has good reaction activity and thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the X-ray diffraction (XRD) crystal phase structure analysis spectrum of the catalyst carrier obtained in Example 1.
[0027] Figure 2 This is an X-ray diffraction (XRD) crystal phase structure analysis spectrum of the catalyst sample obtained in Example 1.
[0028] Figure 3 The catalyst carrier obtained in Example 1 was Zn by XRD. 2+ In ZrO 2 Lattice capacity in a crystalline phase.
[0029] Figure 4 The Zn content of the catalyst support was obtained by XPS extrapolation. 2+ In ZrO 2 Lattice capacity in a crystalline phase.
[0030] Figure 5 This is a test chart of the methanol steam reforming hydrogen production performance of the catalyst sample obtained in Example 1.
[0031] Figure 6 This is the selectivity diagram for hydrogen production from methanol steam reforming of the catalyst sample obtained in Example 1.
[0032] Figure 7 is the H of the catalyst sample obtained in Example 1 2 -TPR test chart.
[0033] Figure 8 The threshold catalyst 7% CuO / Zn in the catalyst sample obtained in Example 1 0.4 Zr 0.6 O x Stability test chart. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. Example 1
[0035] Prepare 4g of carrier, weigh Zn(NO 3 ) 2 ∙6H 2 O and Zr(NO 3 ) 4 ∙5H 2O was added to a beaker, and an appropriate amount of DDI water was added. Heat and stir in a 90°C water bath to dissolve. After complete dissolution, NH 3 ∙H 2 Adjust the pH value to 9 with O. After the precipitate is formed, stir for 2 hours, let it stand for 2 hours, filter it, and wash it with deionized water until the TDS of the filtrate is less than 20 ppm. Dry the filter cake in an oven at 110°C for 12 hours, take it out, and grind it. Put it into a muffle furnace at 550°C and heat it at 2°C / min. -1 The temperature was raised to 550°C and then maintained for 4 hours to obtain the final catalyst support.
[0036] To prepare 2 g of catalyst, 1.86 g of carrier and 0.4252 g of Cu(NO 3 ) 2 ∙3H 2 Add an appropriate amount of DDI water to the crucible and stir for 2 hours. Heat and stir in a 90℃ water bath to evaporate to dryness. Place in a 110℃ oven until completely dry. Place in a 450℃ muffle furnace at 2℃ / min. -1 The temperature was raised to 450 °C and then maintained for 4 hours to obtain the final catalyst. Example 2
[0037] In order to quantify Zn 2+ In ZrO 2 The solubility in the crystalline phase was determined by XRD and XPS extrapolation of the catalyst support obtained in Example 1. The specific method is as follows: the strongest ZnO (101) peak intensity and the ZrO peak intensity of each support were measured. 2 (111) peak intensity to obtain the relative intensity I ZnO(101) / I ZrO2(111) Ratio, with ZnO content as the horizontal axis, relative intensity I ZnO(101) / I ZrO2(111) The ratio is used as the ordinate to fit a linear regression line. It can be seen that the intersection of the regression line and the X-axis is 0.457 g ZnO / g ZrO 2 , that is, the Zn / Zr molar ratio is 41 / 59, which indicates that Zn 2+ Can replace up to 41% of Zr 4+ Formation of ZnZrO x At the same time, the XPS extrapolation method is used to verify the XRD extrapolation results, and the Zn 2p 3 / 2 Peak height and Zr 3d 1 / 2 The ratio of the peak height is taken as the y-axis, and the ZnO content is taken as the x-axis, which is 0.494 g ZnO / g ZrO 2 When , the two fitting lines intersect, that is, the molar ratio of Zn to Zr is 43:57, which is basically consistent with the XRD extrapolation result. Example 3
[0038] A Zn x Zr 1-x O y Application of Cu-based catalyst with solid solution as carrier in hydrogen production by methanol steam reforming. The catalyst sample obtained in Example 1 was used to evaluate the reaction performance of the methanol steam reforming hydrogen production system. The specific implementation method is as follows: 100 mg of catalyst with a mesh size of 40-60 was placed in a fixed bed quartz tube reactor, and 10 vol% H was introduced at a flow rate of 30 mL / min under the conditions of 1 atm and 300 °C. 2 / Ar mixed gas reduction for 40 minutes, the reaction temperature is controlled at 200-360℃, and the temperature is controlled by a thermocouple. 3 OH / H 2 The H O molar ratio was 1 / 1.5 and the flow rate was 0.05 mL / min. 2 O and CH 3 The OH mixture was injected into the vaporization chamber by a micro pump and the temperature was controlled at 200°C to completely evaporate the liquid into gas. The corresponding reaction space velocity (WHSV) was 42000 mL / h˙g cat Then, Ar was introduced into the reactor at a flow rate of 30 mL / min for reaction. The gaseous mixture in the product was first condensed by a cold water trap, and then passed into a GC9310 gas chromatograph equipped with a TDX-01 column and a TCD detector for online analysis using 99.99% Ar as a carrier gas to monitor H 2 , CO 2 The concentration of CO and carbon balance was used to calculate the reaction conversion rate, and in the catalyst activity test, three measurements were taken at each temperature to take the average value, and the error was controlled within 2.0%. Example 4
[0039] The catalyst sample obtained in Example 1 was subjected to H 2 -TPR characterization to explore the redox properties of the catalyst. Zn x Zr 1- x O y The carrier has no obvious reduction peak, 7%CuO / Zn x Zr 1-x O y The catalyst H 2 The consumption peak is caused by the reduction of CuO. It can be seen that with the increase of ZnO content, the reduction temperature of the sample increases from 196℃ to 207℃, and the catalyst CuO / Zn 0.4 Zr 0.6 O xIt has the highest reduction temperature. When the ZnO content exceeds the threshold, the reduction temperature drops to 192℃, indicating that CuO, ZnO and ZrO 2 The interaction between them increases with the increase of ZnO content. When the threshold is exceeded, the reduction temperature decreases, which proves that the interaction between metals is weakened. Example 5
[0040] For the lattice capacity threshold of 7% CuO / Zn 0.4 Zr 0.6 O y The catalyst was subjected to a stability test, and the catalyst was reacted at a reaction temperature of 240° C. for 50 hours.
[0041] The experimental results are as follows Figure 1 , 2 As shown, Example 1 successfully prepared Zn x Zr 1-x O y solid solution, and CuO is loaded to obtain a solid solution Zn x Zr 1-x O y CuO was successfully loaded on Zn x Zr 1-x O y On the carrier. Figure 3 , 4 It can be seen that the Zn obtained in Example 1 x Zr 1-x O y XRD and XPS extrapolation of solid solution support gave Zn 2+ In ZrO 2 Solubility in the crystalline phase. Figure 5 , 6 It can be seen that the catalytic activity of methanol steam reforming hydrogen production by the samples obtained in Example 1 has obvious differences, among which the threshold catalyst 7% CuO / Zn 0.4 Zr 0.6 O y It has the best reactivity and lower CO selectivity. Figure 7 This shows that the threshold catalyst 7%CuO / Zn obtained in Example 1 0.4 Zr 0.6 O y The interaction between the metal and the support is the strongest, which may be the reason why the catalyst in Example 3 has the best performance. Figure 8 It shows that the catalyst with the best reaction performance in implementation case 3 is 7%CuO / Zn 0.4 Zr 0.6 O yIt has good thermal stability. After reacting at 240℃ for 50 hours, the hydrogen production rate of the catalyst decreased slightly, and CO 2 The selectivity was maintained above 98%.
Claims
1. A copper-based / solid solution catalyst for methanol reforming to produce hydrogen, characterized in that Solid solution Zn x Zr 1-x O y The Cu-based catalyst as a carrier has a molecular formula of 7%CuO / Zn x Zr 1-x O y , wherein x=0.1~0.7, preferably x=0.4; When Zn x Zr 1-x O y When the content of ZnO in each gram of ZrO2 in the solid solution carrier is less than 0.457 grams, the carrier exhibits a tetragonal zirconia crystal phase. When the solubility exceeds this value, the excess ZnO 2+ ZnO crystallites will be formed.
2. A copper-based / solid solution catalyst for methanol reforming to produce hydrogen according to claim 1, characterized in that The 7%CuO / Zn x Zr 1-x O y , x=0.
4.
3. The method for preparing a copper-based / solid solution catalyst for hydrogen production from methanol reforming according to claim 1, characterized in that The following steps are involved: (1) According to the Zn / Zr molar ratio, weigh Zn(NO3)2∙6H2O and Zr(NO3)4∙5H2O into a beaker, add an appropriate amount of deionized water, heat and stir in a 90℃ water bath to dissolve into a clear solution; (2) Add 25-28 wt.% ammonia water dropwise to the solution obtained in step (1) while stirring to adjust the pH value to 9. After the precipitate is formed, stir for 2 h, let stand for 2 h, filter and wash with deionized water until the TDS of the filtrate is less than 20 ppm; (3) drying the filter cake obtained in step (2) in an oven at 110° C. for 12 hours, taking it out, and grinding it; (4) The product obtained in step (3) was placed in a muffle furnace and heated at a rate of 2°C / min. It was calcined at 550°C in an air atmosphere for 4 h to obtain Zn x Zr 1-x O y Solid solution carrier; (5) Weigh the solid solution carrier prepared in step (4) and Cu(NO3)2∙3H2O into a crucible, add an appropriate amount of deionized water, stir for 2 h, heat and stir in a 90°C water bath to evaporate to dryness, place in a 110°C oven until completely dried, and then grind; (6) The product obtained in step (5) was placed in a muffle furnace and heated at a rate of 2°C / min, and calcined at 450°C in an air atmosphere for 4 h to obtain a Zn x Zr 1-x O y Cu-based catalysts with solid solution as support; (7) Quantification of Zn using XRD and XPS extrapolation x Zr 1-x O y Solute Zn in solid solution 2+ ions in the ZrO2 lattice, obtaining the optimal ratio of Zn x Zr 1-x O y Cu-based catalysts with solid solution as support.
4. Use of the copper-based / solid solution catalyst for hydrogen production by methanol reforming as claimed in claim 1 in hydrogen production by methanol steam reforming.